Diagnostic Dilemma: Adult Onset Still’s Disease Mimicking Lymphoma—A Case Report and Literature Review - Mohannad N. AbuHaweeleh (22928704) (2025)
Introduction Adult‐onset Still’s disease (AOSD) is a rare systemic inflammatory condition with hallmark features of spiking fevers, arthritis, and a salmon‐colored maculopapular rash. It typically affects young adults, with a bimodal age distribution of 15–25 and 36–46 years. The prevalence of AOSD ranges from 1 to 34 cases per million people, with an incidence rate of 0.16–0.4 per 100,000 individuals. AOSD’s etiology remains unclear but is thought to involve genetic and environmental factors. Diagnosis relies on clinical criteria, such as the Yamaguchi criteria, and exclusion of other conditions. Misdiagnosis is common, particularly in regions where infections and malignancies with overlapping features are prevalent. This case report highlights a diagnostically challenging case of AOSD in a young woman, emphasizing the importance of thorough evaluation and accurate diagnosis. Case Presentation A 21‐year‐old female with no prior comorbidities presented with persistent fever, a transient salmon‐colored rash, and polyarthritis involving the wrists, shoulders, ankles, and small joints. Three months prior, she had been treated for left submandibular sialadenitis attributed to mumps. Laboratory work revealed elevated C‐reactive protein (CRP), ferritin, and LDH levels with a normal erythrocyte sedimentation rate (ESR) and autoimmune profile. Imaging studies, including PET‐CT, suggested malignancy, raising suspicion of lymphoma. However, lymph node biopsy showed reactive hyperplasia without evidence of malignancy. Ultimately, a diagnosis of AOSD was established based on clinical and laboratory findings. The patient was initiated on anakinra and prednisolone, leading to significant improvement. At a 2‐month follow‐up, she had complete resolution of symptoms. Conclusion AOSD presents a significant diagnostic challenge due to its rarity and symptom overlap with infections, malignancies, and autoimmune diseases. This case highlights the importance of a thorough clinical evaluation and the application of established diagnostic criteria to facilitate early diagnosis and timely management. Other Information Published in: Case Reports in Immunology License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1155/crii/5533371